Ventricular arrhythmia burden during different physical activities in patients with arrhythmogenic right ventricular cardiomyopathy: Preliminary analysis - Fernando G. Beltrami; Kyle G. P. J. M. Bolye; Corinna Brunckhorst; Firat Duru; Christina M. Spengler; Ardan M. Saguner (Bern Open Publishing, 2024)
Introduction Patients suffering from arrhythmogenic right ventricular cardiomyopathy (ARVC) should avoid intense endurance exercise to reduce the risk of adverse cardiac events and disease progression. On the other hand, an active lifestyle might be preferable to a sedentary one, which also brings a host of complications. Evidence for safe levels of physical activity in ARVC, however, is scarce. This is study aimed to describe the ventricular arrhythmia burden - estimated as the prevalence of premature ventricular contractions (PVC) - of different exercise modalities and intensities on ARVC patients. Methods The pilot analysis includes four (1F, 33 ± 12 yrs, BMI 24 ± 4 kg/m2) ARVC patients harboring a pathogenic plakophilin-2 variant and carrying an implantable cardioverter-defibrillator performed different exercises while monitored via 12-lead ECG. The order of modalities was randomized and participants instructed to stop when surpassing perceived exertion of 15 on the Borg 6-20 scale. Resistance exercises included two-legged squats and single arm biceps curls (each with 20 repetitions and 2 min duration) while endurance exercise included 5 min of treadmill walking, 3 min cycling bouts at heart rate (HR) of 80, 100 and 120 bpm as well as cycling at 120 bpm with 2 additional min of active cool down. Blood lactate concentration was assessed at the end of the cycling bouts. Results No adverse cardiac event were noted and no exercise was terminated for medical reasons. During walking HR was 76 ± 8 bpm, whereas PVC burden was 11 ± 6% (range 4-18%). Cycling at 82 ± 4 bpm induced a PVC burden of 7 ± 5% (range 3- 14%), which increased to 13 ± 8% (range 3- 21%) at 93 ± 2 bpm and further to 16 ± 16% (range 7-37%) at 105 ± 3 bpm. In all three modalities the PVC burden was higher in the first 3 min of recovery than during the activity itself. Adding a 2 min active cool down increased the PVC burden to 25 ± 16% (range 6-45%). 2-legged squats performed at 101 ± 15 bpm had a PVC burden of 9 ± 12%, which increased to 19 ± 14% at recovery. One arm biceps curls at 75 ± 13 bpm had a PVC burden of 4 ± 3% during the activity and 9 ± 5% during recovery. Perception of effort varied widely when cycling at 80 bpm (range 6-12) or 100 bpm (range 8-14), but less so at 120 bpm (range 13-15). Blood lactate concentration when cycling at 120 bpm ranged between 2.2 and 3.5 mmol/L, typically associated with exercise in the "heavy" intensity domain. Discussion/Conclusion ARVC patients present a high, intensity-dependent PVC burden during exercise and short-term recovery. However, we observed widely different PVC burdens and perceived exertion at a given HR during different exercise modalities, which calls for personalized recommendations on physical activity. Exercises with small muscle mass seem to minimize the PVC burden and training the different muscles separately could be an interesting avenue to maintain physical fitness in ARVC patients.